Getting Somalia wrong? : faith, war and hope in a shattered state - Harper, Mary, 1965-; International African Institute; Royal African Society; Social Science Research Council (U.S.) (London ; New York : Zed Books ; New York : Distributed in the USA exclusively by Palgrave Macmillan, 2012)
"Somalia is a failed state, representing a threat to itself, its neighbours and the wider world. In recent years, it has become notorious for the piracy off its coast and the rise of Islamic extremism, opening it up as a new 'southern front' in the war on terror. At least that is how it is inevitably portrayed by politicians and in the media. In Getting Somalia Wrong? Mary Harper presents the first comprehensive account of the chaos into which the country has descended and the United States' renewed involvement there. In doing so, Harper argues that viewing Somalia through the prism of al-Qaeda risks further destabilizing the country and the entire Horn of Africa, while also showing that though the country may be a failed state, it is far from being a failed society. In reality, alternative forms of business, justice, education and local politics have survived and even flourished. Provocative in its analysis, Harper shows that until the international community starts to 'get it right' the consequences will be devastating, not just for Somalia, but for the world."--Publisher's website.
Clan and country -- History -- Islamism -- A failed state? -- Piracy -- Somalia and the outside world.
Published in association with International African Institute, Royal African Society, Social Science Research Council.
Includes bibliographical references (p. [208]-209) and index.
Keywords: Somalia -- History -- 1991-; Somalia -- Politics and government -- 1991-; Somalia -- Social conditions -- 1960-